Analysis of Sayyid Qutb's Tafsir on the Concept of Istiá¹Ä'ah in Hajj - Asep Fuad (UIN Sunan Gunung Djati Bandung, 2023)
One of the conditions for the obligation to perform the pilgrimage to the Baitullah is only for those who can afford it (istiá¹Ä'ah). The meaning of istiá¹Ä'ah includes several things, including; Al-istiá¹Ä'ah al-mÄliyah, second, al-istiá¹Ä'ah al-badÄniyah, and third, al-istiá¹Ä'ahal-amniyyah. Studying istiá¹Ä'ah in Tafsir Qur'Än and Islamic fiqh is significant because it determines how much a person is obliged to carry out God's commands. Regarding the interpretation and views of some scholars and mufasir figures regarding the concept of istaá¹Ä'ah, if it is related to the situations and conditions that occurred in the pilgrims in Indonesia, then several obstacles or opportunities hinder their intention to carry out the pilgrimage and umrah. Departing from these problems, the author seeks to explore the concept of istiá¹Ä'ah in the pilgrimage in the Qur'an using the interpretation of Fi Zhilalil Qur'Än. The research method used in this article is a descriptive analysis based on library research. The results of this study are that Istiá¹Ä'ah is a condition in which a person has financial provisions, masters the knowledge of Hajj rituals, has a sincere heart, is patient, grateful, trusts and humbles', and is mentally and physically healthy.